Implementasi Peraturan Daerah (Perda) Nomor 12 Tahun 2008 tentang Retribusi Parkir Kendaraan Kabupaten Jember terhadap Sistem Retribusi Parkir Berlangganan - Musa Hidin; Abdul Jabar (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
An implementation is a form seen after a policy is issued. Policy implementation emphasizes that change, act control, and compliance are important concepts in the implementation procedure. Whereas the process of establishing regional regulations regarding vehicle parking fees is not in accordance with legal usefulness, and the implementation of the Regional Regulation on Vehicle Parking Charges for the Regency of Jember which was stipulated and promulgated on October 22, 2008, turned out to be ineffective, the community should be able to benefit from this regulation by regulating a subscription parking system. However, the community is in fact disadvantaged by the double withdrawal when they want to use parking, there are many irregularities in the Perda on Vehicle Parking Charges, especially in the formation and application of Subscribed Parking Charges.